(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the level of knowledge regarding the nursing process among nursing students at Thang Long University in 2025, and to assess their attitudes toward the application of the nursing process in clinical nursing practice. Subjects and methods: A descriptive cross-sectional study was conducted at Thang Long University from August 2024 to August 2025 among 232 nursing students enrolled in the master’s and bridging programs who were involved in patient care. Convenience sampling was applied. Data were collected using a structured questionnaire comprising three sections: demographic and professional characteristics, knowledge (38 true/false items), and attitudes (20 items on a 5-point Likert scale), with internal consistency reliability (Cronbach’s Alpha > 0.7). Knowledge and attitude scores were categorized based on a 75% cutoff of the total score. Data were processed using SPSS 20.0 software and analyzed using descriptive statistics. Results: Most participants demonstrated moderate (56.5%) or good (43.1%) knowledge of the five-step nursing process, with the highest proportion of good knowledge in the assessment step (65.9%). The step with the highest proportion of poor knowledge was implementation (22%). Regarding attitudes, 59.9% of students showed a generally positive attitude toward applying the nursing process in clinical care. Most expressed belief in its purpose and effectiveness, and reported willingness to implement it. However, 40.1% expressed reservations, primarily related to the perceived complexity, excessive paperwork, and inadequacy of current documentation systems. Conclusions: Nursing students at Thang Long University demonstrated predominantly moderate to good levels of knowledge about the nursing process. While overall attitudes toward application were positive, concerns remain about the process’s complexity, administrative burden, and the suitability of current documentation systems.